2013
DOI: 10.1364/ao.52.006906
|View full text |Cite
|
Sign up to set email alerts
|

Long-wavelength mid-infrared reflectors using guided-mode resonance

Abstract: We have proposed and fabricated a new mid-infrared reflector using the guided-mode resonance (GMR). The GMR reflector consists of subwavelength Ge grating on GaAs substrate with a low-refractive-index SiOx layer in between. With a total thickness of about 2 μm, a near-100% reflectivity at 8 μm has been obtained both theoretically and experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…That is, as the diffracted rays couple into the guided mode of grating, a resonant condition can be met to make the reflected light interference constructively so nearly 100% reflectivity could be achieved. 24,27 Ge is chosen as the grating material for two reasons: its refractive index at 8 lm is as high as 4.0 and it is transparent in the mid-IR regime (>2 lm). The underneath SiO x layer is needed to provide the guiding effect in the Ge grating/waveguide because of its low refractive index.…”
Section: A Design Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, as the diffracted rays couple into the guided mode of grating, a resonant condition can be met to make the reflected light interference constructively so nearly 100% reflectivity could be achieved. 24,27 Ge is chosen as the grating material for two reasons: its refractive index at 8 lm is as high as 4.0 and it is transparent in the mid-IR regime (>2 lm). The underneath SiO x layer is needed to provide the guiding effect in the Ge grating/waveguide because of its low refractive index.…”
Section: A Design Conceptmentioning
confidence: 99%
“…[19][20][21] Previously, we have demonstrated both theoretically and experimentally that a high-reflectivity (>95%) GMR mirror at 8 lm can be realized by 2-lm-thick Ge/SiO x on GaAs substrate. 27 In this paper, we propose and analyze a RCE-QDIP consisting of a bottom DBR mirror of 1.5-periods Al 2 O 3 /GaAs, a top GMR mirror of Ge/SiO 2 , and a cavity of a conventional n-i-n QDIP in between. As we shall present, this RCE-QDIP with total thickness of about 7.7 lm is promising to solve the problem of low quantum efficiency in conventional QDIPs in a flexible way.…”
Section: Introductionmentioning
confidence: 99%
“…Foley et al have shown that silicon/SiO 2 ridges' grating exhibited high reflectivity (70%) in the 13-16 μm band [23]. Lai et al have designed a 2D germanium/SiO 2 triangular holes grating showing very high reflectivity (95%) at 8 μm [24].…”
Section: Introductionmentioning
confidence: 99%